Solid Phase Extraction and HPLC Analysis of Pymetrozine Residues in Green Tobacco Leaves - Shan, Juju; Cheng, Xinsheng; Huang, Lan; Chen, Xu (Asian Journal of Chemistry, 2010)
A new method to determine the residues and persistence of pymetrozine in green tobacco leaves is developed. The pymetrozine residues levels were evaluated by extracting using acetonitrile/ water, clean-up using two SPE cartridges and analyzing by HPLC. Average recoveries ranged from 97-99 %, with RSDs below 2.1 %. The limit of detection (LOD) was 0.005 μg mL-1. In field trial, pymetrozine was treated with spraying and irrigation, respectively. Data indicated that higher residues of pymetrozine were found in 1-2 weeks after used the pesticide. After 4 weeks, the residues were lower than the guidance residue limit (GRLs). An analytical method for the determination of pymetrozine residues in green tobacco leaves has been developed. Pymetrozine poses low residues and transitory persistence in green tobacco leaves under the recommended dose.